Educational attainment and anxiety in middle-aged and older Europeans - Chlapecka, Adam; Wolfová, Katrin; Fryčová, Barbora; Cermakova, Pavla (Scientific reports, 2023)
We examined the relationship between educational attainment (EA) and anxiety symptoms in a sample of 77,792 individuals (median age = 64 years, 55% female) from the Survey of Health, Ageing and Retirement in Europe. Using logistic regression, we estimated odds ratio (OR) with 95% confidence interval (CI) for the association between EA (7 educational levels based on International Standard Classification of Education) and anxiety symptoms (12 or more points from the shortened 5-item version of the Beck Anxiety Inventory), adjusting for sociodemographic and health-related factors. We further explored whether the relationship varied by region, sex and age group. Independent of sociodemographic and health-related factors, higher levels of EA were associated with lower odds of anxiety symptoms. The magnitude of this association plateaued at first stage of tertiary education (OR 0.40; 95% CI 0.35-0.47, p < 0.001). The association was stronger in females, middle-aged individuals and in Central and Eastern Europe while not apparent in Northern Europe. Our findings suggest that individuals with higher education might be protected against anxiety throughout life. The protective effect of education against anxiety symptoms is more pronounced in less egalitarian regions and in females.
Keywords: senioři; Middle Aged; mužské pohlaví; European People; ženské pohlaví; Evropané; Humans; úzkost; Educational Status; Female; Aged; stupeň vzdělání; Anxiety; lidé; Male; lidé středního věku